Discursos sobre a leitura em memes: a ‘vergonha’ e o ‘orgulho’ de ser leitor - Silva, Jeniffer Aparecida Pereira da (Universidade Federal de São Carlos, 2021)
In this dissertation, we report the results of the master's research we conducted in the Postgraduate Program in Linguistics at UFSCar with the Laboratory of Reading Studies (LIRE-CNPq), coordinated by Prof. Dr. Luzmara Curcino. In our research, we reflect on the discourses that circulate among us about reading, from the analysis of what is enunciated about it in the form of a current genre: the internet memes. Assuming from the assumption that much of what we know and reproduce about reading goes back, according to Chartier (1998) and Abreu (2001, 2006), to a history of long duration, in which is inscribed everything that we enunciate about this practice, we seek, in our analysis, to survey and analyse some of these discourses mobilized in memes that have reading as a theme. For this survey and analysis, we went through, albeit very briefly, aspects of the history of reading in Brazil, in order to understand the historical, cultural and social reasons that guide what is said about this practice and about us, Brazilians, as readers. The Memes, despite their contemporaneity, like any cultural production, are historically and culturally determined and therefore, disseminate discourses that are shared collectively, that circulate as consensus among us, thus acting as another vector for their propagation. In order to evaluate possible regularities and differences that the meme could disseminate as to the way of enunciating about reading, we used theoretical contributions dedicated to the analysis of discourses about reading, such as Britto (1999, 2008), Barzotto and Britto (1998), Abreu (2001, 2006) and Varella and Curcino (2014), as well as in the perspective of Discourse Analysis of Foucault (1990) concerning the ways of apprehension of the operation of the discourse order that regulates the enunciable and the effects of its circulation, thus affecting the processes of subjectivation of subjects and their practices and the construction of discursive consensus on reading. We also work with authors who discuss and clarify fundamental aspects of the functioning of the meme, relating to its characteristics as a genre (BAKHTIN, 2010), the multimodality and homology of image and verbal languages that in general constitute it (CURCINO, 2011); the detachability of the culture of the fragment (MAINGUENEAU, 2015), its belonging to the field of humour (POSSENTI, 2020); to its peculiar mode of actualization of the author function (FOUCAULT, 2011; CURCINO, 2016a; ROSIN; CURCINO, 2015); finally, to its properties related to circulation, viralization, its replication and dissemination by social networks (ZOPPI-FONTANA, 2018, 2016; KOMESU, 2005; GAMBARATO; KOMESU, 2018; KOMESU; GAMBARATO; TENANI, 2018) among others. The research corpus consisted of 115 memes, of which 51 were actually cited or properly analysed throughout this dissertation. We concluded that the memes, despite remaining faithful to many of the hegemonic discourses about reading, in some cases tend to subvert certain representations, through humorous language plays and also through new visions about reading proposed by their constructors. This, however, is far from being a rule. Most of the time, the memes analysed are aligned with the discourses that commonly guide what can be said about the practice of reading.
Discourses on memes reading: the 'shame' and the 'pride' of being a reader
Keywords: Discursos sobre a leitura; Análise do discurso; Mídias digitais; Memes; Discourses on reading; Discourse analysis; Digital media; LINGUISTICA, LETRAS E ARTES::LINGUISTICA